Modeling the structural equations of human resource management training in the healthcare sector in critical conditions based on the experiences of COVID-19 - Majid Kamali Ardakani; Hamid Taboli; Malikeh Beheshtifar (Shahid Beheshti University of Medical Sciences, 2024)
Background: Human resources at all levels of the organization are the main force behind building the foundation, which plays a role in providing good services with ability, clearer vision, and greater awareness. The aim of study was to model the structural equations of human resource management training in the medical sector in crisis conditions based on the experiences of COVID-19. Methods: This study was cross-sectional and using the structural equation modeling on higher education institutions. The statistical population included 202 experts from higher education institutions. The sample size was 127 people using Morgan's table, who were selected among 202 people by stratified random sampling. Data was analyzed using Smart PLS software. Result: A total of 6 dimensions can be useful for teaching human resource management in crisis situations. The findings demonstrated that the Cronbach's alpha coefficient was greater than 0.70 and that the total dependability of all constructs was strong. According to the path analysis, the training route for human resource management has the most effects when it comes to strengthening transformational decision-making and handling crisis circumstances. The benchmark values for mild, medium, and strong were 0.19, 0.33, and 0.67, respectively. The coefficient of determination of innovative thinking has a weak, interaction to create coherence, emotion management and capacity building for resilience has a moderate, and deepening transformative decision-making and reactive organizational development has a strong. Conclusion: The results showed that human resource training has an active role in human resource participation and crisis management and planning to solve it.